Percutaneous Coronary Intervention (PCI) in Patients with Chronic Total Occlusion (CTO): A Single Center Experiences - Islam, AHMW; Munwar, S; Talukder, S; Reza, AQM (Cardiovascular Journal, 2010)
Background: Aim of the study was to evaluate the primary in-hospital success and 30-days survival outcome of PCI in patients with CTO lesions, using either Bare-metal stents (BMS) or Drug Eluting Stent (DES) like Sirolimus-eluting or Paclitaxel-eluting stent in our hospital setting. Methods: Total 50 patients were randomized as per the definition of CTO, from a total of 400 patients who had PCI at our center in the quantifying period. After the guidewire crossing and the balloon dilation, measurement of the culprit lesion was done by using Siemens QCA measuring system. Among the patients, Male: 41 and Female: 9. Mean age were for Male: 53.3yrs, for Female: 64.4 yrs. Associated CAD risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking. Results: Our study results show 50 patients (12.5%) had CTO lesion out of total 400 PCI procedures. Sex distribution in male 41 (82%), Female 9 (18%). Among the study group; 38 (76%) were Dyslipidemic, 31 (62%) were hypertensive; 20 (40%) patients were Diabetic, 9 (22%) were all male smoker, 5 (10%) were having positive FH for CAD. Female patients were more obese and developed CAD in advance age (male: 53.5 Versus Female: 64.4 yrs). Average diameter of stented vessel was greater in RCA than LAD and LCX. We found that the incidences of CTO lesions were more in LAD territory 20 (40%) followed by RCA 17 (34%) and LCX 13(26%). Single vessel Disease (SVD) in 45 (90%) patients was more common type of CTO lesion followed by Double vessel disease (DVD) in 5(10%). Post procedural, in-hospital and 30 days survival out comer was 100% in our present study. Conclusion: Our study has revealed that PCI in patients with CTO lesions has increased inhospital and 30 days survival outcome, are treated with BMS or DES. The incidence of CTO lesion is more common in male than in female. Female are developing heart disease in advance age and are more obese. Keywords: Chronic total occlusion; PCI; Drug Eluting Stent; Bare Metal Stent DOI: 10.3329/cardio.v2i2.6634 Cardiovasc. j. 2010; 2(2) : 168-174